Thrombin induces pro-inflammatory and anti-inflammatory cytokines secretion from human mast cell line (HMC-1) via protease-activated receptors. (January 2022) - Fang, Xiaobin; Li, Mengmeng; Zhang, Weiyi; Li, Jingyi; Zhu, Tao
Highlights: Increased production of TNF-α, IL-2, INF-γ, IL-6, IL-4, and IL-13 in HMC-1 cells induced by thrombin. Involvement of PAR1, PAR4, and MAPKs, in HMC-1 cells induced by thrombin. Mast cells exhibit dual activation properties after thrombin stimulation. The MAPK signalling pathway is a potential target for thrombin-related events. Abstract: Thrombin-induced mast cell activation represents cross-talk between coagulation and inflammation. However, there is still controversy concerning the pro- or anti-inflammatory effects mast cells have in response to thrombin signaling. Human mast cell HMC-1 was incubated with 0.2 U/mL thrombin. Cells and supernatants were collected. Production of pro- and anti-inflammatory mediators was determined by quantitative PCR (qPCR) and enzyme-linked immunosorbent assay (ELISA). Expression of proteinase-activated receptor-1 (PAR1) and -4 (PAR4) mRNA in HMC-1 cells was analyzed by qPCR. Activation of mitogen-activated protein kinases (MAPKs) was measured by immunoblotting. Furthermore, the impact of PAR1 inhibitor (SCH79797) and agonist (TFLLR-NH2 ), PAR4 inhibitor (BMS986120) and agonist (AYPGKF-NH2 ), and MAPK inhibitors (SB203580, PD98059, and SP600125) on the production of mediators was evaluated using qPCR and ELISA. Thrombin exposure increased pro- and anti-inflammatory mediators, expression of PAR1 and PAR4 mRNA, and phosphorylation of JNK, p38, and ERK1/2 MAPKs in HMC-1 cells. SCH79797, BMS986120, and MAPK inhibitors (SB203580, PD98059, and SP600125) were inhibited, while TFLLR-NH2 and AYPGKF-NH2 promoted pro- and anti-inflammatory cytokines in this process. HMC-1 produces pro- and anti-inflammatory cytokines after thrombin incubation, namely PAR1 and PAR4. Alongside HMC-1, MAPK signaling pathways are involved in the production of these mediators. The mast cells showed dual activation after thrombin stimulation.